The computer in dental office - Sicangco, Ma. Teresa M.V
This is an informative paper looking into the efficiency of a computer and its possible role in the dental office. It starts by familiarizing the reader with the components of a computer system, followed by evidences of its speed and efficiency in dental office transactions and finally it provides some guidelines in the selection of a computer system suitable to the dental office. The author believes that the computer can indeed be a tool in the efficient management of the dental office and that the advantages it offers will in the long run outweigh its capital and operating costs.